A cytocompatible microporous Sr-doped titanium dioxide coating fabricated by plasma electrolytic oxidation - Zheng, Hongming; He, Shuangjun; Zhou, Lijian; Yuan, Jintao; Jiang, Boyi; Ni, Xiaohui; Lu, Kaihang; Zhang, Pengpeng; Zhao, Quanming (Frontiers in Materials, 2023)
Titanium has broad application prospects in the field of hard bone tissue repair and replacement due to its low density, an elastic modulus similar to that of human bone, and better biocompatibility than stainless steel and cobalt-based alloys. However, titanium is a biologically inert material with low biological activity. After implantation, it only physically bonds with bone instead of chemically bonding, which causes complications such as implant loosening. In this study, a strontium-doped titanium dioxide coating was prepared on a titanium surface with micro-arc oxidation. Based on a systematic study of the surface properties of the strontium-doped titanium dioxide coating, the biocompatibility and bioactivity of the coating were evaluated with in vitro cell experiments. The results showed that the strontium-doped titanium dioxide coating was successfully prepared on the titanium surface and exhibited strong bonding with the substrate. The coating surface had a porous structure, and the strontium was dispersed on the surface and inside the coating. The strontium ions were released slowly, which improved the corrosion and wear resistance of the titanium. In vitro cell experiments showed that the coating had good cell compatibility; it promoted the adhesion, proliferation and differentiation of MC3T3-E1 cells and exhibited good biological activity. These results showed that preparation of a strontium-doped titanium dioxide coating by micro-arc oxidation is feasible. The coating had a good surface morphology, improved the biological activity of the titanium and has good potential for clinical application.